Gingerol and shogaol on red ginger rhizome (Zingiber officinale var. Rubrum) using high-performance liquid chromatography - Johan Sukweenadhi; Putu Diah Damitasari; Kartini Kartini; Pissa Christanti; Evanie Noor Putri (Universitas Ahmad Dahlan, 2023)
Red ginger (Zingiber officinale var. Rubrum) is one of the traditional medicines of the Zingiberaceae family, which contains phenolic ketone compounds, including gingerol and shogaol. At high temperatures, gingerol compounds become unstable and will change into shogaol. This study optimized conditions for the simultaneous separation of 6-gingerol, 8-gingerol, 10-gingerol and 6-shogaol from the red ginger extract using the High-Performance Liquid Chromatography method. The analytical conditions consisted of five different methods by modifying the composition of the mobile phase, the elution system, the flow rate of the mobile phase and the optimum UV wavelength. The best conditions for the simultaneous separation using a ratio of water: acetonitrile mobile phase in method 4 with a gradient elution system including 0 min (65:35); 1.5 min (40:60); 5-6.5 min (10:90); 7.5–9 min (0:100); 9.5–12 min (65:35); the mobile phase flow rate was 1.1 mL/min at an optimum wavelength of 230 nm with a retention time of 6-gingerol compound, 6-shogaol, 8-gingerol and 10-gingerol respectively were 4.947; 6.168; 6.554; and 7.412 min and its resolution were 2.267; 1.575; 1.315; and 2.215. Then the tailings factor and asymmetry values were obtained with an average value of ± 1.